SUPLEMENTASI KELAPA KOPYOR TERHADAP AKTIVITAS SUPEROKSIDA DISMUTASE DAN PATOLOGI ANATOMI HATI TIKUS AKIBAT PERLAKUAN PARASETAMOL - Akhmad Endang Zainal Hasan; Hasim Hasim; Agus Setiyono; Sekar Winahyu Ariadini (Universitas Pakuan, 2013)
This research aimed at determining of the effects of the induction of paracetamoland kopyor coconut on the activity of superoxide dismutase (SOD) and pathologicanatomy of rats liver. Previous research shows that paracetamol caused negative effectto the body while kopyor coconut has the ability to improve human health, related to itscapacity to prevent oxidative damage of human body. In this research, the positiveeffect of kopyor is approached through measurement of body weight and the activity ofthe total SOD enzyme of animals tested, which are induced by paracetamol and fed withkopyor. Rats administered with temulawak were positive control. The result showedthat paracetamol treatment using toxic dose was found to reduce body weight of testedanimals. Meanwhile, both kopyor and temulawak supplements were able to counter thenegative effect of paracetamol, indicated by the increase in the body weight of testedanimals. Other results showed that treatments with temulawak and 5 times-dose ofkopyor supplement demonstrated a significantly high total SOD activity in the liver ascompared to negative control. Furthermore, pathologic observation of the testedanimals liver showed that 5 time-dose of kopyor treatment was confirmed to improve the recovery of the liver caused by negative effect of paracetamol, better than the negative control.Key words: kopyor coconut, superoxide dismutase, free radical, pathologic